Introduction to special issue on optional case marking in Tibeto-Burman - Chelliah, Shobhana L. (2024)
This volume is the outcome of the workshop on Optional Case Marking in Tibeto Burman held in conjunction with the Himalayan Languages Symposium at the School of Oriental and Asian Studies (London, September 3rd, 2010). The purpose of the workshop was to discuss agentive case in Tibeto-Burman, focusing on the factors linked to motivation for pragmatic case marking, the terminology used to describe agentive case,